Studies on the effects of growing substrates and physical factors in sweet pepper forcing in context with the generation of calcium deficiency symptoms - Lantos, F.; Pék, Z.; Monostori, Z.; Helyes, L. (International Journal of Horticultural Science, 2010)
In the publications available for us, exact levels of physical factors and those of the growing technology determining Ca2+ deficiency are rarely detailed. Although the influencing role of the various environmental factors (humidity, light, temperature) is known, we had only little information about their exact values which could be presented for the growing practice. Sweet pepper varieties of the same type grown in various substrates responded to the environmental factors in different ways. Our results revealed that increasing temperature of the root zone had the most significant effect on the incidence of Ca2+ -deficient fruits. Their amount, however, gave different results depending on the growing substrate. In forced sweet pepper grown in soil the proportion of Ca2+ - deficient fruits were significantly lower compared to the plants grown on rockwool. Fruits derived from forcing on perlite, in container were damaged the least by the blossom end rot deficiency symptoms. Our experimental results and technological suggestions are based on measurement results of three years.